DOUBLE BURDEN IN THE ERA OF GLOBALIZATION: THE CASE OF WOMEN WORKERS IN INDONESIA - Ardelia, Dela; Pramiyanti, Alila (TOPLAMA, 2025)
This study aims to analyze the double burden phenomenon experienced by working women in Indonesia in the era of globalization, focusing on how the gender division of labor, role conflict, and structural and cultural factors affect their social welfare. The approach used is mixed methods by combining a nationwide quantitative survey and qualitative analysis through in-depth interviews, focus group discussions, and participatory observation. The research subjects consisted of women workers in the formal and informal sectors with an age range of 30-50 years, education levels from elementary school to bachelor's degree, and married marital status. Data analysis was carried out in stages through descriptive statistics, regression, and thematic analysis, then integrated through triangulation to strengthen the validity of the results. The research findings show that the majority of women workers face a double workload, namely the responsibility of public work for an average of eight hours per day, as well as domestic work that remains attached to them. This triggers fatigue, stress, and role conflicts that have an impact on well-being. The results of the discussion confirm that the double burden phenomenon is closely related to patriarchal structures, global capitalism, and the lack of social policy support. In conclusion, gender-sensitive policies, redistribution of domestic roles, and recognition of the value of care work are needed to reduce inequality and improve the welfare of working women in Indonesia.